K teorii a praxi českého mluvnictví - Uličný, Oldřich (Slavistična revija, 2010)
The author discusses the optimal project for Czech grammar. The first part of the article is a critical survey of various understandings of the concept of "grammar" in Czech, Slavic and non-Slavic linguistics circles, in which the author also utilizes the Czech terminological pair mluvnice vs. gramatika. The second part of the article discusses various concepions of the description of Czech as a Slavic and as an inflectional language.
Keywords: češčina; grammar; pragmatika; slovnica; teorija; theory